Pediatric fascial plane blocks: an educational review with technique, tips & tricks - Can Aksu; Hadi Ufuk Yörükoğlu; Sevim Cesur; Alparslan Kuş (BMC Anesthesiology)
Abstract Pain management in pediatric patients is of utmost importance to ensure their well-being and prompt recovery. Current analgesia methods are not always sufficient, leading to suboptimal pain control and increased morbidity. Almost 80% of patients undergoing surgery experience postoperative pain. Results of many studies show that treatment of postoperative pain in children is inadequate. As such, in recent years, there has been growing interest in fascial plane blocks. Fascial plane blocks involve the injection of local anesthetics into the fascial planes surrounding targeted nerves, providing prolonged analgesia with reduced risk of systemic side effects. Studies have shown the efficacy of fascial plane blocks in providing effective analgesia for a variety of surgical procedures, including abdominal, thoracic, and orthopedic surgeries. With careful patient selection and appropriate technique, use of fascial plane blocks in pediatric patients can improve the quality of postoperative pain management, reducing the risk of adverse effects associated with systemic analgesics or well-known classical neuraxial regional anesthesia techniques. In addition to better pain control, the use of fascial plane blocks, as a part of multimodal analgesia regimen, may also reduce the need for opioid analgesics, thereby decreasing the risk of opioid-related adverse effects such as respiratory depression. In conclusion, fascial plane blocks represent a promising alternative to traditional analgesia methods for pediatric patients undergoing surgery. While further research is needed to establish their safety and efficacy for specific procedures in pediatric patients, the available evidence suggests that they may offer significant benefits in terms of pain management. Although fascial plane blocks are volume-dependent techniques, to minimize the risk of local anesthetic systemic toxicity, it is advisable to avoid using more than 0.3–0.5 mL/kg of local anesthetic and to prefer lower concentrations.